Objective Video Quality Assessment of Direct Recording and Datavideo HDR-40 Recording System - Nofia Andreana; Arif Nursyahid; Eni Dwi Wardihani (JAICT, 2016)
Digital Video Recorder (DVR) is a digital video recorder with hard drive storage media. When the capacity of the hard disk runs out. It will provide information to users and if there is no response, it will be overwritten automatically and the data will be lost. The main focus of this paper is to enable recording directly connected to a computer editor. The output of both systems (DVR and Direct Recording) will be compared with an objective assessment using the Mean Square Error (MSE) and Peak Signal to Noise Ratio (PSNR) parameter. The results showed that the average value of MSE Direct Recording dB 797.8556108, 137.4346100 DVR MSE dB and the average value of PSNR Direct Recording and DVR PSNR dB 19.5942333 27.0914258 dB. This indicates that the DVR has a much better output quality than Direct Recording.